Brain-Based Learning dalam Pendidikan Islam Strategi Pembelajaran Berbasis Otak - Kartika, Dewi; Nurjayanti, Gita (Prodi Pendidikan Keagamaan Islam, 2025)
Brain-Based Learning (BBL) is an approach that emphasizes the optimization of brain function in the learning process and is highly relevant to Islamic education. This article aims to describe the application of BBL and emphasize its contribution to the development of students' cognitive, affective, and spiritual domains. This study was conducted through a literature review, examining various sources that discuss the concepts and implementation of BBL in Islamic education. The findings indicate that BBL supports the development of critical thinking skills, creativity, and active engagement of students through the stages of perception, reflection, and application, which align with the concepts of nadzar, ta’qil, and tadabbur. The application of BBL is relevant from early childhood education to higher education and is adaptable in the context of inclusive education. The implications of the study emphasize the importance of teacher training, curriculum, and policies based on neuroscience and Islamic values to ensure that the implementation of BBL is consistent, effective, and applicable.